2019
DOI: 10.1002/clc.23272
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation after hospitalization for myocardial infarction or cardiac surgery: Assessing patient interest, confidence, and physician prescribing practices

Abstract: Background Prioritizing and managing multiple behavior changes following a cardiac hospitalization can be difficult, particularly among smokers who must also overcome a serious addiction. Hypothesis Hospitalized smokers will report a strong interest in smoking cessation (SC) but will receive little assistance from their physicians. Methods We asked current smokers hospitalized for an acute cardiac event to prioritize their health behavior priorities, and inquired about their attitude toward SC therapies. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
(63 reference statements)
0
9
0
1
Order By: Relevance
“…Continued smoking following an MI is a significant driver of future mortality and morbidity (e.g. Boggon et al, 2014;Chow et al, 2010) and experiencing a major cardiac event, such as an MI, can be a driver of quit intentions and attempts (Riley et al, 2018(Riley et al, , 2019, but this experience may not be sufficient to promote successful sustained abstinence (Gaalema et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Continued smoking following an MI is a significant driver of future mortality and morbidity (e.g. Boggon et al, 2014;Chow et al, 2010) and experiencing a major cardiac event, such as an MI, can be a driver of quit intentions and attempts (Riley et al, 2018(Riley et al, , 2019, but this experience may not be sufficient to promote successful sustained abstinence (Gaalema et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, si bien los pacientes hospitalizados dejan de fumar voluntaria o involuntariamente (debido a políticas de hospitales libres de humo de tabaco), la mayoría vuelve a hacerlo después del alta 23 , 24 . Esto constituye una verdadera oportunidad perdida, ya que múltiples trabajos han demostrado que las personas que son hospitalizadas por un problema vinculado a la adicción del tabaco se encuentran más receptivas a la hora de recibir consejos para cesar su adicción 25 , 26 .…”
Section: Discussionunclassified
“…Consideration of these statistics may help persuade some young patients to quit smoking. In addition, the period of great receptivity for smoking cessation intervention is the period following an acute cardiac event and this is the time period where interventions should take place 68 . Although it has been reported that rate of providing tailored evidence‐based interventions is low, 68 this appears to be an approach that should be encouraged to foster long‐term smoking cessation.…”
Section: Discussionmentioning
confidence: 99%